Development of Phonetique Du Français Teaching Materials for Microlearning in The UNJ French Language Education Study Program - Ismail, Subur; Ratna; Widiasuti, Wahyu Tri; Andika, Yunilis (Future Science, 2023)
This research is based on observations from Phonétique du français lectures which show that students still have difficulty understanding the content of the lecture material. This is due to the fact that most of the sources of lecture material are reference books and journal articles with a high level of French at a minimum level of B1, especially since the lecture language is in French. Meanwhile, students' French level is still low, equivalent to A2 level. For this reason, this research was conducted to overcome problems in Phonétique du français lectures by developing Phonetique du francais teaching materials for micro learning. To develop phonétique du français teaching materials, the EDDIE method is used which includes 5 stages, namely; analysis stage, design stage, development stage, implementation stage, and evaluation stage. In this research, only the analysis stage to the design stage was carried out. At the analysis stage, an analysis is carried out which includes: 1) an Analysis of the number of lecture hours, 2) Analysis of learning objectives, 3) an Analysis of the coverage of Phonétique du français lecture material, 4) an Analysis of the micro learning model used. The design stage includes learning objectives, lecture material content, selected assessment methods and frequency. Thus, this research is only at the design stage, namely the development of phonetique du francais teaching materials by CECRL which uses micro learning (infographics, explanatory videos, short videos, and podcasts). The results of this research have implications for the Phonétique du français lecture process which is designed according to CECRL and according to students' French language skills and microlearning methods that can motivate students to understand the content of Phonétique du français lectures.